2015
DOI: 10.1073/pnas.1512812112
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric activation of M 4 muscarinic receptors improve behavioral and physiological alterations in early symptomatic YAC128 mice

Abstract: Mutations that lead to Huntington's disease (HD) result in increased transmission at glutamatergic corticostriatal synapses at early presymptomatic stages that have been postulated to set the stage for pathological changes and symptoms that are observed at later ages. Based on this, pharmacological interventions that reverse excessive corticostriatal transmission may provide a novel approach for reducing early physiological changes and motor symptoms observed in HD. We report that activation of the M 4 subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…Pancani et al reported that chronic administration of VU0467154 beginning at a pre-symptomatic age (2 months old) could prevent the appearance of deficits in both glutamatergic and dopaminergic neurotransmissions in 5 months old YAC128 mice models of Huntington's disease. 42) Motor coordination deficits and locomotor hypoactivity were also prevented by chronic treatment in YAC128 mice. Additionally, Shen et al reported that the M 4 mAChR PAM VU10010 blocks aberrant long-term potentiation in direct-pathway spiny projection neurons in an L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesia (LID) mice model.…”
Section: Current Topicsmentioning
confidence: 93%
“…Pancani et al reported that chronic administration of VU0467154 beginning at a pre-symptomatic age (2 months old) could prevent the appearance of deficits in both glutamatergic and dopaminergic neurotransmissions in 5 months old YAC128 mice models of Huntington's disease. 42) Motor coordination deficits and locomotor hypoactivity were also prevented by chronic treatment in YAC128 mice. Additionally, Shen et al reported that the M 4 mAChR PAM VU10010 blocks aberrant long-term potentiation in direct-pathway spiny projection neurons in an L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesia (LID) mice model.…”
Section: Current Topicsmentioning
confidence: 93%
“…Extensive studies in rodents and non-human primates suggest that these actions of M 4 PAMs on striatal plasticity could provide therapeutic benefits in treating L-DOPA-induced dyskinesia in Parkinson's disease (Shen et al, 2016). Furthermore, M 4 PAMs can normalize excessive excitatory transmission at cortico-striatal synapses in rodent models of Huntington's disease and chronic administration of M 4 PAMs prevents the appearance of motor deficits in these animals (Pancani et al, 2015). Finally, the ability of M 4 PAMs to reduce behavioral effects of cocaine suggest that these agents may be useful for the treatment of substance abuse disorders (Dencker et al, 2012).…”
Section: Potential Utility Of Muscarinic Receptor Pams For Treatment mentioning
confidence: 99%
“…M 4 (muscarinic acetylcholine receptor subtype 4) positive allosteric modulators (PAMs) represent an exciting therapeutic strategy to treat multiple domains of schizophrenia, 1-18 as well as other CNS disorders, 19,20 via a new molecular mechanism. 21 However, the great potenital has been hampered by limited chemical diversity centered on a 3-amino-thieno[2,3- b ]pyridine core, as in 1 - 4 , (Figure 1), which engenders steep SAR, species differences (rat versus human M 4 PAM potency, affinity/cooperativity and subtype selectivity), poor solubility, and/or low CNS penetration.…”
mentioning
confidence: 99%